2009
DOI: 10.2174/156652409788167140
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives for Melanoma Immunotherapy: Role of IL-12

Abstract: Metastatic melanoma is a poor prognosis skin cancer. Since conventional treatments including surgery and chemotherapy often fail, novel therapeutic strategies are needed. In particular, identification of melanoma associated antigen has fostered the progress of both active (vaccines) and adoptive immunotherapy. Some promising results have been obtained, but most melanoma patients are not yet cured possibly because of different immune-escape mechanisms operated by tumor cells. Several studies have addressed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Furthermore, as stated above, regulation of CD8 ϩ T-cell immunity is not dependent on IFN-␥, as reported for other infections (9,11). Recent studies have suggested that due to its ability to expand the CD8 ϩ T-cell population, IL-12 treatment has a strong therapeutic potential in diseases where these cells are critical for the host defense (3,27). As CD8 ϩ T-cell immunity plays a central role in protection against E. cuniculi challenge (1, 2, 16), the observations described above have strong implications in developing strategies for designing immunotherapeutic agents for HIV-infected and elderly individuals who are prone to this type of infection.…”
Section: Fig 8 Augmentation Of the Il-12-mediated Cd8supporting
confidence: 56%
“…Furthermore, as stated above, regulation of CD8 ϩ T-cell immunity is not dependent on IFN-␥, as reported for other infections (9,11). Recent studies have suggested that due to its ability to expand the CD8 ϩ T-cell population, IL-12 treatment has a strong therapeutic potential in diseases where these cells are critical for the host defense (3,27). As CD8 ϩ T-cell immunity plays a central role in protection against E. cuniculi challenge (1, 2, 16), the observations described above have strong implications in developing strategies for designing immunotherapeutic agents for HIV-infected and elderly individuals who are prone to this type of infection.…”
Section: Fig 8 Augmentation Of the Il-12-mediated Cd8supporting
confidence: 56%
“…Since cancers possess several strategies to evade immune surveillance, the application of immunotherapy is of a great importance (Weber, 2011). For example, interleukin(IL)-12 and interferon-γ (IFN-γ) are among the best characterized and most potent antitumor cytokines (Cocco et al, 2009;Balachandran and Adams, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has profound antitumor efficacy that was demonstrated on a variety of different types of tumors and metastases in preclinical as well as clinical studies. In recent years, several excellent reviews describing the activities of IL-12, the preclinical and clinical use of recombi-nant IL-12 and gene therapy with IL-12 have been published [1,8,11,45,56,57]. On the other hand, 10 years have passed since the first paper on combination of plasmid DNA encoding for IL-12 injected intramuscularly with electroporation was published [39].…”
Section: Introductionmentioning
confidence: 99%